Challenges for Restoration of Coastal Marine Ecosystems in the Anthropocene - Abelson, Avigdor; Reed, Daniel C.; Edgar, Graham J.; Smith, Carter S.; Kendrick, Gary A.; Orth, Robert J.; Airoldi, Laura; Silliman, Brian; Beck, Michael W.; Krause, Gesche; Shashar, Nadav; Stambler, Noga; et al. (Frontiers in Marine Science, 2020)
Coastal marine ecosystems provide critical goods and services to humanity but many are experiencing rapid degradation. The need for effective restoration tools capable of promoting large-scale recovery of coastal ecosystems in the face of intensifying climatic stress has never been greater. We identify four major challenges for more effective implementation of coastal marine ecosystem restoration (MER): (1) development of effective, scalable restoration methods, (2) incorporation of innovative tools that promote climate adaptation, (3) integration of social and ecological restoration priorities, and (4) promotion of the perception and use of coastal MER as a scientifically credible management approach. Tackling these challenges should improve restoration success rates, heighten their recognition, and accelerate investment in and promotion of coastal MER. To reverse the accelerating decline of marine ecosystems, we discuss potential directions for meeting these challenges by applying coastal MER tools that are science-based and actionable. For coastal restoration to have a global impact, it must incorporate social science, technological and conceptual advances, and plan for future climate scenarios.